Giorgio Agambens Paulus og “the return of religion” - Mortensen, Jacob Bliddal (Dansk Teologisk Tidsskrift, 2016)
In recent years, the Italian philosopher Giorgio Agamben has received more and more attention. Political philosophers increasingly discuss his political philosophy, and theologians and biblical scholars discuss his book on Paul and Paul’s letter to the Romans. This article situates the work of Agamben (especially on Paul) within a broader philosophical and theoretical context. Furthermore, it provides an interpretation of Agamben’s Paul in relation to his concept of “messianism” and in relation to a broad movement within continental philosophy called “the return of religion”. Finally, this article discusses some of the hermeneutical implications of a “philosophical Paul” or a “Paul ofthe philosophers”.